?HYDROTHERMAL CRYSTALLIZATION AND CRYSTAL GROWTH OF a-Si02 FROM RICE HUSK SILICA ASH IN ALKALINE SOLUTIONS - Korashy, SA EL (Biological Sciences - PJSIR, 1998)
White pure and active amorphous silica was prepared from rice husk with 99.96% purity by acid leaching and pyroly- sis. This silica could be crystallized into prismatic microcrystalline a-Si02 (n-88nm) under hydrothermal conditions (215 °C::::-20 atm. press.) from alkaline solutions. The maximum yield of a-Si02 was obtained at O. 6 molar ratio of NaOH I Si02 which reduced to O. 2 in the presence of AP+ and lor B3+traces. This is due to the formation of silicalite crystals (considered to be a polymorph of Si02). It has been found that transition metal cations in the reaction media affects the degree of a-Si02 crystallization in the order: Fe3+> Ni2+> Cr3+> amorphous Si02 > C02+> Cu2+;:’ Mn2+> Zn2+> Zr4+> La3+.Both mechanism of a-Si02, silicalite growth and ions incorporation were discussed.